2022
DOI: 10.3390/jcm11082123
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Short Daily Hemodialysis with Physidia S3 System: Clinical Performance Assessment during the Training Period

Abstract: Background: A growing body of scientific evidence indicates that clinical outcomes of hemodialysis patients can be improved with short daily dialysis treatment. Current in-center hemodialysis machines do not fulfill the requirements needed for self-care home hemodialysis (HHD) treatment. In line with the reviviscence of home therapy, several hemodialysis devices have been developed and deployed for treatment. Physidia S3 is one of these new dialysis delivery systems featuring an appealing design and functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Patients’ perspectives also appeared to be improved throughout the study follow-up period. The patient perception and satisfaction survey previously reported by our group confirmed that the S 3 system was easy to use, easily implemented at home, and facilitated patients’ mobility [ 13 ]. Despite the short daily treatment schedule, the S 3 system was considered as a less intrusive treatment modality than previously experienced with in-center hemodialysis treatments.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Patients’ perspectives also appeared to be improved throughout the study follow-up period. The patient perception and satisfaction survey previously reported by our group confirmed that the S 3 system was easy to use, easily implemented at home, and facilitated patients’ mobility [ 13 ]. Despite the short daily treatment schedule, the S 3 system was considered as a less intrusive treatment modality than previously experienced with in-center hemodialysis treatments.…”
Section: Discussionmentioning
confidence: 64%
“…The Physidia S 3 system (named the S 3 system) is a bagged delivery cycler and portable communicating dialysis monitoring device specifically designed for short daily hemodialysis (HHD) and self-administered treatment [ 13 ]. The S 3 device has a compact and portable cubic design (dimension 40 × 40 × 40 cm), weighing less than 25 kg and being specifically designed for short daily low-dialysate-flow HHD (dialysate flow rates of 150 to 200 mL/min).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 There is now increasing evidence that the prognosis of HD patients can be improved by increasing the number or duration of HD sessions. [10][11][12][13][14] In this regard, the application of short-daily in-center HD (SDH) (2-3 h, five or more sessions per week) may provide promising advantages compared with CHD as it appears to attenuate HD-related adverse effects. [10][11][12][14][15][16] SHD appears to reduce chronic inflammation and left ventricular hypertrophy and is associated with better phosphorus control when compared with CHD.…”
Section: Introductionmentioning
confidence: 99%
“…Several devices, including the Physidia S3 (ref. 19 ), Quanta SC 20 and NxStage 21 , are in clinical use and the DIMI 22 device is undergoing clinical testing. Various initiatives to improve and/or miniaturize home haemodialysis devices are currently underway 23 , including the development of dialysis membranes to enable longer and more effective blood purification, systems to mimic selective ion transport in the nephron 24 and sorbents and membranes for dialysate regeneration 25 .…”
Section: Introductionmentioning
confidence: 99%